Labour in global value chains in Asia - Dev Nathan, Ed (Development trajectories in global value chains, 2016)
"Brings together a set of studies of labour conditions in GVCs - in labour-intensive sectors, medium- and high-technology sectors and knowledge-intensive sectors"--Provided by publisher"--